SP1-Mediated Upregulation of circFAM126A Promotes Proliferation and Epithelial-Mesenchymal Transition of Oral Squamous Cell Carcinoma via Regulation of RAB41 - Wang, Jun; Ouyang, Shaobo; Zhao, Siyu; Zhang, Xianhua; Cheng, Mingyang; Fan, Xin; Cai, Ying; Liao, Lan (Frontiers in Oncology, 2022)
Background: Accumulating evidence indicates that circular RNAs have major roles in the progression of human cancers. Nevertheless, the molecular mechanism and effects of circFAM126A in oral squamous cell carcinoma (OSCC) remain unclear. Methods: Quantitative real-time PCR (qRT-PCR) was used to detect expression levels of circFAM126A in OSCC tumor tissues and cell lines; the effects of circFAM126A small hairpin RNA (shRNA) on the proliferation, migration, and invasion of OSCC cells were detected by MTT, colony formation, and transwell assays; xenograft mouse models were used to determine the effects of circFAM126A shRNA on the growth of OSCC tumors in vivo; the expression of miR-186 and RAB41 in OSCC tissues and cells was examined by qRT-PCR; the targeting relationship between circFAM126A and miR-186 was verified by dual-luciferase reporter and RNA pull-down assays; and the relationship between miR-186 and RAB41 was explored. Results: The expression of circFAM126A was significantly upregulated in OSCC tissues and cells. The transcription factor SP1 transcriptionally activated circFAM126A. However, knockdown of circFAM126A markedly suppressed the proliferation, migration, and invasion of OSCC cells in vitro and inhibited tumor growth and distant metastasis in vivo. Moreover, circFAM126A increased the expression of RAB41 and promoted its mRNA stability via binding to miR-186 and RNA-binding protein FUS. Overexpression of RAB41 antagonized the effects of circFAM126A knockdown and induced an aggressive phenotype of OSCC cells. Conclusion: SP1 transcriptionally activated circFAM126A modulated the growth, epithelial-mesenchymal transition (EMT) of OSCC cells via targeting the miR-186/FUS/RAB41 axis, suggesting that circFAM126A is a potential biomarker for the treatment of OSCC.